Doing nothing is not an option! : facing the imminent labor crisis - Critchley, Robert K.
"The changes in composition of the U.S. workforce and many other developed economies is unavoidable. Many CEOs choose to ignore the figures given the current economic climate. Other managers may suggest that outsourcing or increased immigration will solve the problem." "Bob Critchley, author of Rewired, Rehired, or Retired? has examined an abundance of statistics and research and offers practical solutions to this seismic shift in the workforce. Many of the solutions offered require little more than a policy change and a change in attitude. Bob provides numerous examples of real organizations that have implemented his solutions and their results."--BOOK JACKET.